Signifikansi Keamanan Maritim Di ASEAN - Arfin Sudirman, Muhammad Ridho (Mandala: Jurnal Ilmu Hubungan Internasional, 2020)
In order to securitizing maritime issues in the Southeast Asian region, ASEAN plays a significant role as a regional organization through three aspects as an instrument, arena and independent actors. Each aspect shows the seriousness of ASEAN in facing traditional and non-traditional maritime security threats. ASEAN created several mechanisms to maintain maritime security in the Southeast Asian region. However, the implementation of regional maritime law enforcement policies is an obstacle for ASEAN, including the differing views of some ASEAN member countries in addressing traditional and non-traditional maritime security threats. Moreover, with the principle of non-intervention of ASEAN on member countries, conditions have increasingly complex in ASEAN's efforts to strategically empowering maritime security of the Southeast Asian region.